A Constant Rotating Kerr-Newman Black Hole with No Net Electrical Charge (Global Journal of Science Frontier Research, 2017)
A black hole solution for the rotating electrical charge gives the Kerr-Newman metric. Incorporation of the oscillating effects show to drive rotation. The model derived permits the consideration of an electrical charged BH with no net charge, which would neutralize. From the solutions a new complete set of tensor elements to modify the Kerr-Newman metric leading to the feature the squared line element can represent a black hole permanently carrying electrical charge, but not evenly distributing and spreading on the surface. Due to its properties, the black hole approached in this theory shows serrated in a kind sawtooth boosting the idea for determination of torsion effects and detect rotation. An exact representation of the data together with an entire set of information can found to support further evaluation of similar objects. The stability of the structure will be discussed.
Keywords: Kerr-Newman metric; tensor elements; electrical charge; stability of the structure